Synthesis and crystal structures of multifunctional tosylates as basis for star-shaped poly(2-ethyl-2-oxazoline)s - Hoogenboom, Richard; Fijten, Martin W. M.; Kickelbick, Guido; Schubert, Ulrich S. (Beilstein Journal of Organic Chemistry, 2010)
The synthesis of well-defined polymer architectures is of major importance for the development of complex functional materials. In this contribution, we discuss the synthesis of a range of multifunctional star-shaped tosylates as potential initiators for the living cationic ring-opening polymerization (CROP) of 2-oxazolines resulting in star-shaped polymers. The synthesis of the tosylates was performed by esterification of the corresponding alcohols with tosyl chloride. Recrystallization of these tosylate compounds afforded single crystals, and the X-ray crystal structures of di-, tetra- and hexa-tosylates are reported. The use of tetra- and hexa-tosylates, based on (di)pentaerythritol as initiators for the CROP of 2-ethyl-2-oxazoline, resulted in very slow initiation and ill-defined polymers, which is most likely caused by steric hindrance in these initiators. As a consequence, a porphyrin-cored tetra-tosylate initiator was prepared, which yielded a well-defined star-shaped poly(2-ethyl-2-oxazoline) by CROP as demonstrated by SEC with RI, UV and diode-array detectors, as well as by 1H NMR spectroscopy.
Keywords: cationic polymerization; crystal structure; living polymerization; star-polymer; tosylate

Star and Hyperbranched Polymers - Mishra, M.; Kobayashi, S. (Marcel Dekker Inc., 1999)

(untitled) - Inoue, K. (Prog. Polym. Sci., 2000)

(untitled) - Kobayashi, S. (Prog. Polym. Sci., 1990)

(untitled) - Aoi, K.; Okada, M. (Prog. Polym. Sci., 1996)

(untitled) - Hoogenboom, R. (Macromol. Chem. Phys., 2007)

(untitled) - Hoogenboom, R. (Angew. Chem., Int. Ed., 2009)

(untitled) - Bloksma, M. M.; Hendrix, M. M. R. M.; Schubert, U. S.; Hoogenboom, R. (Macromolecules, 2010)

(untitled) - Kranenburg, J. M.; Tweedie, C. A.; Hoogenboom, R.; Wiesbrock, F.; Thijs, H. M. L.; Hendriks, C. E.; Van Vliet, K. J.; Schubert, U. S. (J. Mater. Chem., 2007)

(untitled) - Kempe, K.; Jacobs, S.; Lambermont-Thijs, H. M. L.; Fijten, M. W. M.; Hoogenboom, R.; Schubert, U. S. (Macromolecules, 2010)

(untitled) - Kobayashi, S.; Uyama, H.; Narita, Y. (Macromolecules, 1992)

(untitled) - Chang, J. Y.; Ji, H. J.; Han, M. J.; Rhee, S. B.; Cheong, S.; Yoon, M. (Macromolecules, 1994)

(untitled) - Kim, K. M.; Ouchi, Y.; Chujo, Y. (Polym. Bull., 2003)

(untitled) - Jin, R.-H. (J. Mater. Chem., 2004)

(untitled) - Jin, R.-H. (Adv. Mater., 2002)

(untitled) - Schubert, U. S.; Nuyken, O.; Hochwimmer, G. (J. Macromol. Sci., Part A: Pure Appl. Chem., 2000)

(untitled) - McAlvin, J. E.; Scott, S. B.; Fraser, C. L. (Macromolecules, 2000)

(untitled) - Luxenhofer, R.; Bezen, M.; Jordan, R. (Macromol. Rapid Commun., 2008)

(untitled) - Fijten, M. W. M.; Haensch, C.; Van Lankvelt, B. M.; Hoogenboom, R.; Schubert, U. S. (Macromol. Chem. Phys., 2008)

(untitled) - Hoogenboom, R.; Fijten, M. W. M.; Paulus, R. M.; Thijs, H. M. L.; Hoeppener, S.; Kickelbick, G.; Schubert, U. S. (Polymer, 2006)

(untitled) - Hoogenboom, R.; Nakahashi, A.; Kickelbick, G.; Chujo, Y.; Schubert, U. S. (Acta Crystallogr., Sect. E, 2007)

(untitled) - Wiesbrock, F.; Hoogenboom, R.; Abeln, C. H.; Schubert, U. S. (Macromol. Rapid Commun., 2004)

(untitled) - Wiesbrock, F.; Hoogenboom, R.; Leenen, M. A. M.; Meier, M. A. R.; Schubert, U. S. (Macromolecules, 2005)

(untitled) - Blessing, R. H. (Acta Crystallogr., Sect. A, 1995)

SHELX97 Programs for Crystal Structure Analysis, Release 97-2 (Universität Göttingen, 1998)